CLINICODIAGNOSTIC VALUE OF DETERMINATION OF LEPTIN AND ANDROGENIC HORMONES IN BOYS AND TEENAGERS WITH OBESITY - O. G. Verbitskaya; V. A. Popova; A. A. Afonin; A. A. Aleksandrova; P. V. Zolotukhin; T. P. Shkurat (Медицинский вестник Юга России, 2013)
Purpose: To address the relation between the levels of androgenic hormones and metabolic indices in obese male children and adolescents.Materials and methods: 175 boys were examined, of which children at the age of 11-12 – 75 persons, teenagers at the age of 13-15 – 100 persons. Obesity degree according to Knyazev and sexual development stage according to Tanner were evaluated, the following hormones were identified in the blood serum: luteinizing hormone, follicle-stimulating hormone, testosterone, dihydrotestosterone, androstenedione, anti-Müllerian hormone and inhibin B as well as insulin, leptin and lipometabolism rates.Results: In the group of 13-15-year-old boys 20% of boys with obesity had the 1st-2nd stage of sexual development according to Tanner. In children with obesity in the prepubescent age the following was detected: dyslipidaemia, hyperleptinemia and high level of AMH; there are no reliable differences in the level of sex hormones if compared to children with normal weight. 13-15-year-old boys with the 1st-2nd stage of sexual development according to Tanner have the highest leptin rates (among all groups), AMH (in comparison to the same age) and very low rates of sex hormones.Summary: Hyperleptinemia detected at the stage of prepubescent age is an important physiological regulator of a signal to the beginning of pubescence. The heightened level of leptin in boys with obesity in pubescence age as well as the maintained heightened concentration of AMH suppressing the increase of the androgenic hormone level causes the development of prolonged pubescence.